Implementation of the Prospective Bride Course in Indonesia: Provision for Marital Life by Kantor Urusan Agama - Mubarok, Yusup; Sapar, Akhmad; Lestari, Aprida Kurnia; Arrohmatan, Arrohmatan (CV. Tripe Konsultan, 2023)
This study aims to examine the implementation of courses for prospective brides as an effort to improve knowledge of married life in Indonesia. This research uses a literature review method with content analysis techniques of the laws of the government of the Republic of Indonesia, regulations of the Ministry of Religion, and is supported by the opinions of experts in books and journals. The result of this research is that the prospective bride course (Suscatin) is an education for prospective brides that must be followed and carried out by the Marriage Advisory, Development and Preservation Agency (BP4) which is under the auspices of the religious affairs office (KUA) as a representative office of the district or city ministry of religion office throughout Indonesia. The course aims to provide knowledge about the concept of a harmonious family based on Islamic teachings known as Sakinah, Mawaddah Warahmah, and to prevent the occurrence of divorce that often occurs among brides these days. All needs regarding the implementation of the course are covered by funds from both central and regional governments. Implementation guidelines include syllabus, materials, learning models, lesson hours, resource persons, graduation certificates and others are regulated in the Regulation of the Director General of Islamic Public Guidance Number: DJ.II/542 of 2013 concerning Guidelines for the Implementation of Pre-Marriage Courses Article 1 and Article 2.